On the critical behaviour of random anisotropy magnets - Dudka, M.; Folk, R.; Holovatch, Yu. (Condensed Matter Physics, 2001)
The effect of a local anisotropy of random orientation on a ferromagnetic
phase transition is studied. To this end, a model of a random anisotropy
magnet is analysed by means of a field theoretical renormalization group
approach. The one-loop result of Aharony about the absence of a 2nd order
phase transition for isotropic distribution of random anisotropy axis at space
dimension d < 4 is corroborated. Досліджується вплив локальної анізотропії випадкової орієнтації на
феромагнітний фазовий перехід. З цією метою за допомогою методу
теоретико-польової ренормалізаційної групи проведено аналіз моделі магнетика з випадковою анізотропією. Підтверджено однопетлевий результат Агароні про відсутність фазового переходу другого
роду для ізотропного розподілу осі випадкової анізотропії при вимірності простору d < 4 .